Mahatma Gandhi Statue inside Corporation Hall - Ghosh, Ayan (Jio Institute, 2023)
Marble statue of Mahatma Gandhi inside the Corporation Hall. Hanging from the ceiling are microphones marked with numbers for respective speakers, one of the many additions made to suit changing technology. The original stained-glass panels from the bay window have been replaced with metal plaques commemorating Mumbai's history and prominent landmarks.